Optimization of DNA extraction from dental remains. Issue 14 (29th May 2019) - Cafiero, Concetta; Re, Agnese; Stigliano, Egidio; Bassotti, Ezio; Moroni, Rossana; Grippaudo, Cristina
Abstract: Efficient DNA extraction procedures is a critical step involved in the process of successful DNA analysis of such samples. Various protocols have been devised for the genomic DNA extraction from human tissues and forensic stains, such as dental tissue that is the skeletal part that better preserves DNA over time. However DNA recovery is low and protocols require labor‐intensive and time‐consuming step prior to isolating genetic material. Herein, we describe an extremely fast procedure of DNA extraction from teeth compared to classical method. Sixteen teeth of 100‐year‐old human remains were divided into two groups of 8 teeth and we compared DNA yield, in term of quantity and quality, starting from two different sample preparation steps. Specifically, teeth of group 1 were treated with a classic technique based on several steps of pulverization and decalcification, while teeth of group 2 were processed following a new procedure to withdraw dental pulp. In the next phase, the samples of both group underwent the same procedure of extraction, quantification and DNA profile analysis. Our findings provide an alternative protocol to obtain a higher amount of good quality DNA in a fast time procedure, helpful for forensic and anthropological studies.